2017
DOI: 10.1089/jpm.2016.0265
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Home-Based Palliative Care Program in an Accountable Care Organization

Abstract: Background: People with advanced illness usually want their healthcare where they live—at home—not in the hospital. Innovative models of palliative care that better meet the needs of seriously ill people at lower cost should be explored.Objectives: We evaluated the impact of a home-based palliative care (HBPC) program implemented within an Accountable Care Organization (ACO) on cost and resource utilization.Methods: This was a retrospective analysis to quantify cost savings associated with a HBPC program in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
120
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 161 publications
(129 citation statements)
references
References 24 publications
7
120
2
Order By: Relevance
“…Although not universally accessible, palliative care programs that focus on improving quality of life for patients and their families are increasingly available within large hospitals, 25 and are expanding to long-term care 26 and community-based settings. 27 A better understanding of the nature and intensity of EOL caregiving could prove useful to ongoing efforts to monitor and improve access and quality of hospice and palliative care.…”
Section: Introductionmentioning
confidence: 99%
“…Although not universally accessible, palliative care programs that focus on improving quality of life for patients and their families are increasingly available within large hospitals, 25 and are expanding to long-term care 26 and community-based settings. 27 A better understanding of the nature and intensity of EOL caregiving could prove useful to ongoing efforts to monitor and improve access and quality of hospice and palliative care.…”
Section: Introductionmentioning
confidence: 99%
“…17 More recent studies have shown financial benefits from community-based serious illness care. Lustbader et al 18 found that home-based palliative care provided to patients in an ACO was associated with cost savings, reduced hospitalization, and increased hospice use. Another study compared the impact of three community-based oncology care programs that used different models to reduce cost and improve quality of life.…”
Section: Resultsmentioning
confidence: 99%
“…If the process is irreversible in terminal stage patients in ICU, the advances in ICU treatments together with technological developments lead to an increase in severe sequelae in patients by prolonging the process of death [6]. Although there has been an increase in recent years in the delivery of PC services to patients in hospital or care provided at home, it is not clear whether these services have met the PC requirements of these patients and their families [14][15][16].…”
Section: Overwievmentioning
confidence: 99%